EVALUASI PENERAPAN MODEL SENTRA DI PENDIDIKAN ANAK USIA DINI KUMARA ASIH, KARANG SUKUN, MATARAM - Ni Wayan Mariaseh, (Journal of Innovation Research and Knowledge, 2024)
This research aims to determine the discrepancy from Center Model application at Kumara Asih Kindergarten. There are threemain problem in this research including how do the planning of Center Model implementation at Kumara Asih Kindergarten; how do the implementation of Center Model at Kumara Asih Kindergarten; and how do the affectiveness of Center Model implementation at Kumara Asih Kindergarten. Data collection techniques that used in this research were: observation, interview and documentation. This research shown that planning implementation of Center Model at Kumara Asih Kindergarten includes: (a) prepared daily lesson plan; (b) prepared weekly lesson plan; (c) prepared learning center; and (d) organized learning area. Furthermore school needed budget plan to accommodate the innovative toys. The implementation of Center Model at Kumara Asih kindergarten includes: (a) welcoming children; (b) opening play; (c) transitioning; (d) core activities (consisting of before experience playing stage, during experiences playing stage and after playing experience stage); (e) having lunch together; (f) evaluation; and (g) closing activities. The implementation of Center Model was supported by classes outing routine every month, dance and yoga practice every Saturday. The affectiveness of Center Model application shown by the change of students attitude from various aspects such as (a) social emotional; (b) independence; (c) cognitive; (d) skills; (e) communication skills and (f) religion behavior